British Churches and the Cinema in the 1930s - Machin, G. I. T. (Studies in church history, 1992)
With the possible exception of the ‘wireless’, the cinema was the most popular form of entertainment in Britain from the 1920s to the 1950s, when attendances began to decline and cinemas to close because of the competing power of television. On the eve of the Second World War, television was still in struggling infancy, while the number of cinemas had grown from some 3,000 in 1914 to about 5,000 in 1939, some of the recent ones having been built on a palatial scale. The introduction of sound films in 1929 enhanced the cinema’s popularity, and by 1939 annual attendances exceeded 1,500 million. Still higher figures were reached for a few years from 1945.